A Comment on "The Political Consequences of Green Policies: Evidence from Italy" - Florian Caro; Asher Labovich; Chidubem Okechi; David Reinstein; Maria Clara Rodrigues (Institute for Replication (I4R), 2024)
Colantone et al. (2024a) use survey data to examine how a major ban on combustion engine cars in Milan, Italy affected voting behavior of treated car owners. The authors find that the ban raised the probability of voting for the populist right wing Lega party by 15.4-18.3 percentage points, a 70-80% increase relative to the average car owner. The estimate is statistically significant at the 5% level. These effects are driven by dissatisfaction with money losses rather than more antagonistic attitudes towards environmental protection. In this report, we inspect the data and replication package of the paper with two sets of exercises. First, we successfully computationally reproduce all the main results of the paper. Second, we test the robustness of the authors' main results by exploring different definitions of control variables, variations in the regression specifications, and alternative econometric models and research designs. Our results generally confirm the authors' conclusions, but are smaller in magnitude and suggest that the ATTs in the original paper might have been overstated.
Keywords: 330